Gamified interactive e-books for bullying prevention: enhancing knowledge and motivation in Chinese primary schools - Shao, Jiawei; Abdul Rabu, Siti Nazleen; Chen, Chuang (Frontiers in Psychology, 2025)
Bullying is increasingly prevalent in Chinese schools, contributing to a rise in associated criminal cases. A key factor in this trend is the lack of comprehensive understanding of bullying. Studies indicate a clear correlation between the level of understanding of bullying and its frequency. The adverse effects of bullying are expected to persist into adulthood, particularly during the crucial phase of behavioral and cognitive development in elementary school, when children are most receptive to changes in behavior and attitudes. Traditional lecture-based methods used to teach bullying awareness to Chinese primary school students often result in boredom and disengagement, reducing their ability to comprehend and address bullying effectively. This study developed a gamified interactive e-book (GIEB) aimed at enhancing the motivation and anti-bullying knowledge of Chinese primary school students. A quasi-experimental design with pretest and posttest assessments was employed to evaluate the approach’s effectiveness. The study involved 60 third-grade students from a public primary school in Hefei, Anhui Province, China, who were randomly assigned to either an experimental group using the gamified interactive e-books (GIEB group) or a control group receiving traditional lectures (TL group). Findings indicated that the GIEB group showed significant improvements in motivation and understanding of bullying compared to the TL group. This research highlights the potential of gamified interactive e-books as effective educational tools for bullying prevention by making learning more engaging and effective. The practical implications of this study suggest that integrating gamified interactive e-books into the curriculum could significantly enhance students’ motivation to learn about bullying and their anti-bullying knowledge, ultimately contributing to more effective bullying prevention in schools.